Civil service reforms for merit and political neutrality agenda for implementation post revolution administrative reform - Varela, Amelia P. (Philippine Journal of Public Administration, 1988)
The Civil Service Commission (CSC), a constitutional body which functions as the central personnel agency of government is in charge of introducing reforms and strategies aimed at upholding and strengthening merit and political neutrality. Since the Philippine government is undergoing transition from dictatorship to democracy, there is a need to improve and reform the bureaucracy. This, could be done by strengthening and improving the image of the civil service, reducing red tape and corruption, orienting/ reorienting civil servants to values of good administration and reviewing and evaluating existing rules and regulations. But the main issue that has to be resolved by the CSC is how to shield the merit system and career officials, including the CSC itself from spoils politics. Only when this is resolved could there be a responsive, and responsible government which can deliver public services with acceptable efficiency.